ANALISIS BAURAN PEMASARAN DAN STRATEGI PENGEMBANGAN PADA UD RAJA TAPE DI KABUPATEN BONDOWOSO (Agridevina : Berkala Ilmiah Agribisnis, 2022)
UD Raja Tape is one of the tape agroindustry in Nangkaan Village, Bondowoso District, Bondowoso Regency which has problems related to declining sales volume. The decline in sales was due to the large number of tape units entering the market and they had to pay attention to the marketing mix strategy and development strategy for their business to be able to survive in the competition of the tape agroindustry. This study aims to determine (1) the marketing mix and (2) the development strategy at UD Raja Tape in Bondowoso Regency. The method of determination in this study uses the Purposive Method. The research method in this study used descriptive analytic methods. The sampling method in this study used the purposive sampling method. The data collection method in this study used interview, observation, and documentation. The data analysis method in this study uses 2 analytical tools, namely the marketing mix consisting of 4P and SWOT. The results showed: (1) the application of the marketing mix at UD Raja Tape consists of 4P, namely: (a) Product Mix, the tape produced by UD Raja Tape uses cassava butter as raw material, has three packages. (b) Price Mix, a pricing method offered based on competitors' prices. (c) Promotional Mix, using personal selling, advertising and cooperation activities in the form of agents spread across various regions. (d) Place Mix, marketing UD Raja Tape through private outlets and through marketing agencies. (2) strategy development using SWOT analysis conducted at UD Raja Tape shows an alternative strategy applied to UD Raja Tape implementation, namely SO. The strategy that can be applied is to create product innovations with new packaging and flavors and increase product distribution.DOI : https://doi.org/10.33005/adv.v11i1.3155